Bioinformatics Analysis and Functional Verification of ADAMTS9-AS1/AS2 in Lung Adenocarcinoma - Liu, Wei; Luo, Wenguang; Zhou, Peijie; Cheng, Yong; Qian, Liting (Frontiers in Oncology, 2021)
Long non-coding RNAs (lncRNAs) play a critical role as competitive endogenous RNAs (ceRNAs) in biological processes of cancer. However, the roles of specific lncRNAs in ceRNA network of lung adenocarcinoma (LUAD) remains largely unclear. Herein, we identified the roles of lncRNA ADAMTS9-AS1/AS2 (ADAMTS-AS1/AS2) in lung adenocarcinoma by bioinformatics analyses and functional verification. First, differentially expressed gene ADAMTS9-AS1, ADAMTS9-AS2 and ADAMTS9 were screened out from GSE130779. Then the expression correlation of these three genes was analyzed. The results showed that ADAMTS9-AS1, ADAMTS9-AS2 and ADAMTS9 were down-regulated in LUAD, and were positively correlated with each other. Then, miRcode was used to find miR-150 that bind to ADAMTS9-AS1/ADAMTS9-AS2/ADAMTS9. Next, co-expression analysis functional enrichment analyses were performed. The results showed that the differentially expressed genes were mainly enriched in Beta3 integrin cell surface interactions and epithelial-to-mesenchymal transition. Finally, the cell functions of ADAMTS9-AS1 and ADAMTS9-AS2 in A549 and NCI-H1299 cell lines were verified. In vitro cell studies confirmed that ADAMTS9-AS1 and ADAMTS9-AS2 plays an inhibitory role in LUAD cells.